FREQUENCY OF ARDS IN ICU AND CAUSE-RELATED FACTORS - ARSHAD , S; ARSHAD , MS; AKHTAR , A; ISHTIAQ , W; ILYAS , A; QADEER , A (Biological and Clinical Sciences Research Journal, 2024)
Acute Respiratory Distress Syndrome (ARDS) is a severe condition frequently seen in ICU patients, leading to increased morbidity and mortality. Understanding its prevalence and associated risk factors can enhance early detection and improve patient outcomes. Objective: To determine the frequency of ARDS in ICU patients and identify factors contributing to its development. Methods: This cross-sectional study was conducted in the Department of Critical Care from July 2023 to June 2024 after obtaining ethical approval. A total of 76 patients admitted to the ICU were enrolled based on pre-defined criteria. Detailed histories, physical examinations, and diagnostic evaluations, including chest X-rays, CT scans, and laboratory tests, were collected from electronic health records (EHRs). Demographic data and relevant clinical variables were analyzed using SPSS version 26. Statistical tests were applied to assess associations between ARDS development and patient characteristics. Results: Out of 76 ICU patients, 39 met the study inclusion criteria. The mean age was 51.00 ± 15.50 years, with an average hospital stay of 9.38 ± 9.49 days. Males comprised 66.7% (n=26) and females 33.3% (n=13) of the sample. ARDS was diagnosed in 33.3% (n=13) of patients. Stratification of patients by age showed 28.2% aged 20-40 years, 46.2% aged 41-60 years, and 25.6% over 60 years. The duration of ICU stay was 53.8% for 1-5 days, 15.4% for 6-10 days, and 30.8% for more than 10 days. No statistically significant differences in ARDS prevalence were found when stratified by age, hospital stay, or gender. Conclusion: ARDS was identified in 33.3% of ICU patients, highlighting the critical need for early diagnosis and prompt management. The study underscores the importance of addressing predisposing factors to improve patient outcomes. Further research is needed to explore potential therapeutic interventions.